Electric field controlled cohesive symmetric hook-C shape inspired metamaterial for S-band application - Rasheduzzaman, S.; Faruque, M. R. I.; Eistiak, A.; Islam, M. T.; Khandaker, Mayeen Uddin * (Elsevier, 2020)
In this paper, a split ring resonator (SRR) bounded new cohesive symmetric hook-C shaped unit cell is developed. The metamaterial has 4   × 4-unit cell array, which is applicable for s-band application for its high bandwidth (S21 < -10 dB) of 0.6 GHz and high effective medium ratio (EMR) 12.78. Commercially available electromagnetic simulator CST (Computer simulation technology) microwave studio has been utilized at 2.93 GHz resonance frequency in this investigation. The electric field of this design is also observed by modifying the design structure that shows effective results. The new developed hook-C shaped metamaterial is fabricated and measured to validate the simulation results, which is eligible for high performance in long distance communications. The proposed metamaterial is highly recommended to apply in Airport Surveillance Radar (ASR) system for its highly effective medium ratio and size miniaturization.